Composite phase change heat storage material based on porous ceramic surface carbonization modification and preparation process thereof

By carbonizing modification on the surface of porous ceramics, the problems of high cost and complex process in the prior art are solved, and the thermal conductivity and thermal stability of porous ceramics are significantly improved. The prepared composite phase change heat storage materials show more efficient and stable performance in multiple fields.

CN119751127APending Publication Date: 2025-04-04HEBEI UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411935638.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing porous ceramic surface modification methods have shortcomings such as high implementation costs and complex processes, and it is difficult to effectively improve their thermal conductivity and thermal shock resistance.

Method used

By introducing a carbonization layer on the surface of the porous ceramic, surface carbonization modification is performed using a simple and easy method, including cleaning the porous ceramic in anhydrous ethanol solution, impregnating the modified solution, drying and sintering, and finally adsorbing the phase change material under a vacuum environment.

Benefits of technology

Effective adhesion of the carbonization modification of porous ceramic surface is achieved, which significantly improves its thermal conductivity, mechanical strength and thermal stability. The prepared composite phase change heat storage material has more efficient and stable performance in high-temperature heat storage, solar thermal utilization and industrial waste heat recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751127A_ABST
    Figure CN119751127A_ABST
Patent Text Reader

Abstract

The invention discloses a composite phase change heat storage material based on porous ceramic surface carbonization modification and a preparation process thereof, and particularly relates to a porous ceramic surface modification method and a preparation process of the composite phase change heat storage material based on porous ceramic surface carbonization modification. The porous ceramic provided by the invention can be prepared by adopting methods such as freeze casting, sol-gel, foaming, direct calcination and the like, the porous ceramic material can be aluminum oxide, titanium oxide, silicon carbide, silicon oxide and the like, and the modification solution adopts cheap saccharide organic matters or carbonaceous materials as main modification raw materials. The phase-change material can be an organic phase-change material such as paraffin, sugar alcohol and the like, and can also be an inorganic phase-change material such as inorganic salt and the like. The composite phase change heat storage material prepared by the technology shows more efficient and more stable performance in the fields of high-temperature heat storage, solar heat utilization, industrial waste heat recovery and the like. The application of the technology provides a new way for functionalization and sustainable development of the porous ceramic-based composite heat storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a porous ceramic surface modification method and a preparation process of a composite phase change heat storage material based on the carbonization modification of the porous ceramic surface, belonging to the field of phase change heat storage material preparation. Technical Background

[0002] Porous ceramics have become an important research direction in the field of heat storage material preparation due to their excellent thermophysical properties, structural stability and controllable pore structure. However, in order to further improve its thermal performance and application effect, surface carbonization modification technology has gradually attracted attention in recent years. By introducing a carbonized layer on the surface of porous ceramics, its thermal conductivity can be significantly improved, while its resistance to thermal shock and chemical stability can be enhanced. Carbonization modification can not only reduce the thermal resistance of porous ceramics and improve the efficiency of thermal conduction, but also form a protective layer through surface coating to avoid oxidation and degradation of materials during high-temperature heat storage. Carbonized porous ceramics are loaded with phase change materials by vacuum impregnation to obtain ceramic-based composite phase change materials, which show more efficient and stable performance in the fields of high-temperature heat storage, solar thermal utilization and industrial waste heat recovery. The application of this technology provides a new way for the functionalization and sustainable development of porous ceramic heat storage materials.

[0003] Surface modification can effectively improve the heat transfer, mechanical strength, thermal stability and other properties of porous ceramics, impart new functionality without affecting the original structure, and expand its application in high-end fields. Currently, the commonly used methods for surface modification of porous ceramics include vapor deposition (PVD), electrodeposition, coating deposition and other methods. Some existing modification methods have the disadvantages of high implementation cost and complex process. Summary of the invention

[0004] The present invention provides a porous ceramic surface carbonization modification method and a preparation process of a composite phase change heat storage material based on the porous ceramic surface carbonization modification, which has the advantages of strong applicability and low price.

[0005] The present invention is achieved through the following technical solution, which is characterized by comprising the following steps: Step 1: Place the modified porous ceramic into an anhydrous ethanol solution and transfer it to a vacuum drying oven to clean the impurities in the porous structure of the porous ceramic. Step 2: Prepare a modified solution of a certain concentration, completely immerse the cleaned porous ceramics in the solution, and place them in a vacuum drying oven to ensure that the porous ceramics are completely immersed in the modified solution. Step 3: Take out the porous ceramic after impregnation and put it into a blast drying oven to dry. The moisture on the surface of the porous ceramic is removed and the modified solution adheres to the surface of the porous ceramic. The specific time can be further determined according to the best drying effect. Step 4: The porous ceramic is placed in a tubular furnace and sintered in a nitrogen atmosphere. After sintering, the porous ceramic is naturally cooled to obtain a carbonized and modified porous ceramic. Step 5: Immerse the carbonized modified porous ceramic into the molten phase change material to complete adsorption under a vacuum environment, take out the porous ceramic that has adsorbed the phase change material, and obtain a composite phase change heat storage material.

[0006] Furthermore, the porous ceramic has a number of open pores and closed pores, the porosity is between 30% and 90%, and the pore diameters range from micrometers to nanometers.

[0007] Furthermore, the porous ceramic can be prepared by freeze casting (CN 114918406B), sol-gel (CN105884392A), foaming method (CN 118580098A), direct calcination (CN 118479892A) and the like.

[0008] Furthermore, there is no limitation on the size of the obtained porous ceramic.

[0009] Furthermore, the porous ceramic may be made of aluminum oxide, titanium oxide, silicon carbide, silicon oxide or the like.

[0010] Furthermore, the modified solution can be one or a combination of sucrose, glucose, lactose, chitosan, etc., or it can be a solution containing carbonaceous materials, and the carbonaceous materials include one or a combination of carbon powder, carbon black, graphite powder, carbon nanotubes, etc. In addition, a binder such as carboxymethyl cellulose / hydroxyethyl cellulose / sodium alginate / gelatin, etc. needs to be added to the solution containing carbonaceous materials, and the solution is purified water / deionized water.

[0011] Furthermore, the concentration of the modified solution is between 10wt.% and 60wt.%.

[0012] Furthermore, the drying ovens in steps one, two and five are vacuum drying ovens, and step three is an air drying oven.

[0013] Furthermore, the drying time in step 1 and step 3 is 2.0-3.0 hours, and the vacuum degree of the vacuum drying oven is below 5 kPa.

[0014] Furthermore, in step 1 and step 3, the porous ceramic is placed in the drying oven at a temperature between 80°C and 120°C.

[0015] Furthermore, the best drying effect in step three should be that there is no moisture on the surface and inside of the porous ceramic, and the modified solution just sticks to the surface of the porous ceramic.

[0016] Furthermore, the nitrogen concentration in step 4 is greater than or equal to 99.99%, and the nitrogen flow rate during sintering is between 10 and 15 m / s.3 / h.

[0017] Furthermore, the sintering temperature in a nitrogen atmosphere is increased from room temperature to 800° C., the heating rate is 3-6° C. / min, the holding time is 1-2 h, and the sintering is naturally cooled to room temperature.

[0018] Furthermore, the phase change material may be an organic phase change material such as paraffin, sugar alcohol, etc., or an inorganic phase change material such as inorganic salt, etc.

[0019] Furthermore, in step five, the vacuum environment can be achieved with the aid of equipment such as a vacuum drying oven, the vacuum degree is below 5 kPa, and the temperature is greater than the phase change temperature of the selected phase change material.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0021] Compared with the traditional porous ceramic surface modification process, the present invention has a simpler operation process, and the selected raw materials and operating equipment costs are lower. With the help of a simple and easy operation method, the porous ceramic surface is successfully carbonized and modified, and the modified porous ceramic is used to prepare a composite phase change material. Its uniqueness lies in that after the modification, the porous ceramic surface can be well attached with a carbon layer, which has higher mechanical strength, and the heat transfer and thermal stability of the composite phase change material are also improved.

[0022] The present invention can use sucrose, glucose and the like to prepare the modified solution. Compared with other organic substances with the same mass of sucrose (C 12 H 22 O 11 ), glucose (C6H 12 O6) and other carbon elements, and has a better solubility in aqueous solution, the resulting solution also has a certain viscosity, and the price cost is relatively low.

[0023] The modified solution of the present invention contains carbonaceous materials with excellent properties such as carbon powder and carbon black. In order to ensure that the carbonaceous materials can be evenly dispersed in the solution and the solution has good viscosity, a carboxymethyl cellulose / hydroxyethyl cellulose / sodium alginate / gelatin solution is first prepared, and then the selected carbonaceous materials are evenly mixed in the solution. After sintering, the carbonaceous materials can be well attached to the pore structure of the porous ceramic, thereby improving the mechanical strength and thermal stability of the porous ceramic.

[0024] Compared with the non-carbonized modified porous ceramics, the composite phase change material prepared from the modified porous ceramics has better performance in terms of strength, heat transfer and thermal stability.

[0025] The porous ceramic surface modification process of the present invention is simple, and the composite phase change material prepared after modification has significantly improved effect, which is of great significance for improving the performance of porous ceramic-based composite phase change materials and is conducive to the promotion and application and progress and development of the industry. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be involved in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only test images of the embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Attached Figure 1 XRD pattern of modified porous ceramics DETAILED DESCRIPTION The following examples are provided for a better understanding of the present invention, but are not limited to the best mode of implementation, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0027] Implementation Case 1

[0028] In this embodiment, a cylindrical alumina porous ceramic with a height of 5 cm and a bottom diameter of 5 cm is selected, which is prepared by freeze casting, with a porosity of 76%. The porous ceramic is made of alumina, 1wt.% TiO2 is used as a sintering agent, and the porous ceramic has a layered pore structure. Sucrose is selected to prepare the modified solution. The specific preparation process is as follows:

[0029] (1) Place the cylindrical alumina porous ceramic into a beaker containing anhydrous ethanol solution. The alumina porous ceramic should be completely immersed in the anhydrous ethanol solution. Then transfer the beaker to a vacuum drying oven. Set the vacuum drying oven temperature to 80°C, the vacuum degree to 1 kPa, and the drying time to 120 minutes. The purpose is to remove impurities in the pore structure of the alumina porous ceramic.

[0030] (2) Prepare a modified solution: weigh 40 g of sucrose and put it into 160 ml of deionized water. Stir at 800 rpm at room temperature for 1 hour to completely dissolve the sucrose in the deionized water to prepare a 20 wt.% sucrose solution.

[0031] (3) After the porous ceramic is completely immersed in the sucrose modified solution, it is moved into a vacuum drying oven at room temperature, a vacuum degree of 1 kPa, and a time of 120 minutes to ensure that the surface of the porous alumina ceramic fully absorbs the sucrose solution.

[0032] (4) Take out the porous alumina ceramics from the sucrose modified solution, put them into a blast drying oven and set the temperature to 80°C for 180 minutes. Then take out the porous ceramics and place them on filter paper. When the filter paper is removed, there is no water stain on the surface. Put the porous alumina ceramics into a crucible and transfer it to a tube furnace. Adjust the nitrogen gas flow rate to 10m 3 / h, the temperature was raised from room temperature to 800°C at a heating rate of 5°C / min, and then naturally cooled to room temperature. The nitrogen was turned off and the alumina porous ceramics after carbonization modification were taken out.

[0033] (5) The carbonized alumina porous ceramics were placed in a beaker containing molten erythritol solution, transferred to a vacuum drying oven, set the temperature to 140°C, 5 kPa, and taken out after 2 hours to obtain a composite phase change material.

[0034] The surface carbonized alumina porous ceramics were subjected to XRD test. Figure 1 The test results showed that no new substances were produced, proving that the chemical structure of the surface-modified alumina porous ceramics did not change.

[0035] Implementation Case 2

[0036] In this embodiment, a cylindrical alumina porous ceramic with a height of 5 cm and a bottom diameter of 5 cm is also selected, and is prepared by freeze casting. The porosity is 76%. The alumina porous ceramic has a layered pore structure. Carbon black is selected to prepare the modified solution. Step (1) is the same as the above embodiment and will not be repeated. The other specific preparation processes are as follows:

[0037] (2) To prepare a modified solution, first weigh 1.6 g of carboxymethyl cellulose and put it into deionized water. Stir at 800 rpm for 2 h to completely dissolve the carboxymethyl cellulose in the water. Then weigh 40 g of carbon black and put it into 160 ml of deionized water. Stir at 1000 rpm for 1 h at room temperature to fully mix the carbon black in the deionized water to prepare a 20 wt.% carbon black modified solution.

[0038] (3) The porous alumina ceramics are completely immersed in the carbon black modified solution and moved into a vacuum drying oven at room temperature and a vacuum degree of 1 kPa for 120 minutes to ensure that the surface of the porous alumina ceramics is fully adhered to the carbon black modified solution.

[0039] (4) Take out the porous alumina ceramics from the carbon black modified solution and put them into a blast drying oven. Set the temperature to 80°C and dry for 180 minutes. Then take out the porous alumina ceramics and put them on filter paper. Remove the filter paper and there will be no water stains on its surface. Put the porous alumina ceramics into a crucible and transfer it to a tube furnace. Adjust the nitrogen gas flow rate to 10m 3 / h, the temperature was raised from room temperature to 800°C at a heating rate of 5°C / min, and then naturally cooled to room temperature. The nitrogen was turned off and the alumina porous ceramics after carbonization modification were taken out.

[0040] (5) The carbonized alumina porous ceramics were placed in a beaker containing molten erythritol solution, transferred to a vacuum drying oven, set the temperature to 140°C, 5 kPa, and taken out after 2 hours to obtain a composite phase change material.

[0041] Although the specific implementation of the present invention is described in detail in conjunction with the drawings, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A composite phase change heat storage material based on carbonization modification of porous ceramic surface and its preparation process, characterized in that: The modified solution was prepared with sugars and carbon-containing materials as raw materials, and the porous ceramic surface was carbonized through adsorption, drying, nitrogen atmosphere sintering and other steps. After modification, the thermal conductivity, mechanical strength, thermal stability and other properties of the porous ceramic were improved. The prepared composite phase change material showed more efficient and stable performance in the fields of high-temperature heat storage, solar thermal utilization and industrial waste heat recovery. The application of this technology provides a new way for the functionalization and sustainable development of porous ceramic heat storage materials.

2. The carbohydrate material in the modified solution according to claim 1 is one or a combination of sucrose, glucose, lactose, chitosan, etc., and the carbonaceous material in the modified solution is one or a combination of carbon powder, carbon black, graphite powder, carbon nanotubes.

3. The modification method according to claim 1, characterized in that The preparation steps include: Step 1: Place the modified porous ceramic into an anhydrous ethanol solution and transfer it to a vacuum drying oven to clean the impurities in the porous structure of the porous ceramic. Step 2: prepare a modified solution, completely immerse the cleaned porous ceramics into the solution, and place them in a vacuum drying oven to ensure that the porous ceramics are completely immersed in the modified solution. Step 3: Take out the porous ceramic after impregnation and put it into a blast drying oven to dry. The moisture on the surface of the porous ceramic is removed and the modified solution adheres to the surface of the porous ceramic. The specific time can be further determined according to the best drying effect. Step 4: The porous ceramic is placed in a tubular furnace and sintered in a nitrogen atmosphere. After sintering, the porous ceramic is naturally cooled to obtain a carbonized and modified porous ceramic. Step 5: Place the carbonized modified porous ceramic in the molten phase change material, adsorb it in a vacuum environment, take out the porous ceramic that has adsorbed the phase change material, and prepare a composite phase change heat storage material.

4. The operating temperature and vacuum degree of the drying oven according to claim 3, characterized in that: In step 1 and step 3, the temperature range of the drying oven is 80-110°C; in step 5, the set temperature of the drying oven must be greater than the phase change temperature of the phase change material; and the vacuum degree of the drying oven in the above steps must not be greater than 5kpa.

5. The preparation of the modified solution according to claim 3, characterized in that: In step 2, different mass fractions of sucrose or carbonaceous materials are used to prepare the modified solution, wherein sucrose should use water or deionized water as a solvent, and the carbonaceous material should be evenly dispersed in a viscous solution such as carboxymethyl cellulose. The mass fraction of sucrose or carbonaceous materials in the modified solution ranges from 10wt.% to 60wt.%.

6. The phase change material according to claim 3, characterized in that The type of phase change material can be an organic phase change material such as paraffin, alcohol, etc., or an inorganic phase change material such as an inorganic salt, etc.

7. The porous ceramic according to claim 3, characterized in that It can be produced by freeze casting, sol-gel, foaming, direct calcination and other methods.

8. The porous ceramic according to claim 3, characterized in that Alumina, titanium oxide, silicon carbide, silicon oxide and other materials.

Citation Information

Patent Citations

  • Method for preparing porous ceramic heat-insulating material by sol-gel method

    CN105884392A

  • A novel freezing casting device and casting method for preparing porous materials

    CN114918406B

  • Pure alumina porous ceramic preparation method and equipment

    CN118479892A

  • Method for preparing porous ceramic by stirring foaming method

    CN118580098A